Random dsDNA-templated formation of copper nanoparticles as novel fluorescence probes for label-free lead ions detection - Chen, Junhua; Liu, Jie; Fang, Zhiyuan; Zeng, Lingwen (Chemical communications (Cambridge, England), 2012)
A simple label-free method for the detection of Pb(2+) ions with high selectivity and sensitivity has been developed by using random double-strand DNA-templated formation of copper nanoparticles as novel fluorescence probes in aqueous solution.